DIGITAL LITERACY AND RELIGIOUS IDENTITY: PARENTAL MEDIATION OF TECHNOLOGY USE IN ISLAMIC EDUCATION FOR GENERATION ALPHA IN INDONESIA - Hepi Ikmal; Ahmad Hanif Fahruddin; Sholihah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This study examines parental mediation of technology use as an integrated strategy for transmitting Islamic religious identity to Generation Alpha children in rural Indonesia. Drawing on a qualitative case study conducted in Blajo Village, Kalitengah Sub-District, Lamongan, East Java, the research addresses three questions: the nature of the challenges parents face in sustaining Islamic education amid digital disruption; the strategies families employ to navigate those challenges; and how aqidah, ibadah, and akhlak-based Islamic education is operationalized as a digital character formation framework. Data were collected through semi-structured in-depth interviews with seven parent informants and three child informants, twelve non-participant observation sessions, and document analysis, and analyzed using Miles et al.'s interactive model. Guided by Ulwan's tarbiyah framework, Livingstone and Helsper's parental mediation typology, and Potter's media literacy model, the findings identify three challenge dimensions—temporal disruption of Islamic educational rhythms, individualization of prayer practice, and the reflexive effect of parental digital modeling—and four mediation strategy clusters: active temporal structuring, Islamic content facilitation, exemplary digital self-regulation, and communal religious socialization. Two original theoretical contributions are advanced: